2010
DOI: 10.1093/rheumatology/keq275
|View full text |Cite
|
Sign up to set email alerts
|

The skin of patients with systemic sclerosis softened during the treatment with anti-IL-6 receptor antibody tocilizumab

Abstract: Objective. SSc is an autoimmune disease characterized by fibrosis of the skin and internal organs. Although the aetiology remains uncertain, many reports have suggested that IL-6 is involved in SSc pathogenesis. Tocilizumab, an anti-IL-6 receptor antibody, is an anti-arthritis medicine that works through the blockade of IL-6 functions. To examine the effect of tocilizumab on SSc, we administered tocilizumab to two SSc patients.Methods. Two dcSSc patients were administered tocilizumab at 8 mg/kg once a month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 11 publications
3
99
1
4
Order By: Relevance
“…Two SSc patients who were resistant to conventional treatment regimens were administered tocilizumab at 8 mg/kg every 4 weeks. After the treatment, both patients showed softening of the skin with reductions of 50.7% and 55.7% in the total z-score of Vesmeter, a device for measuring the physical properties of the skin [114], and of 51.9% and 23% in the modified Rodnan total skin score [115]. Histological examination showed thinning of the collagen fiber bundles in the dermis.…”
Section: Systemic Sclerosismentioning
confidence: 98%
See 1 more Smart Citation
“…Two SSc patients who were resistant to conventional treatment regimens were administered tocilizumab at 8 mg/kg every 4 weeks. After the treatment, both patients showed softening of the skin with reductions of 50.7% and 55.7% in the total z-score of Vesmeter, a device for measuring the physical properties of the skin [114], and of 51.9% and 23% in the modified Rodnan total skin score [115]. Histological examination showed thinning of the collagen fiber bundles in the dermis.…”
Section: Systemic Sclerosismentioning
confidence: 98%
“…RA (in more than 90 countries worldwide) [36][37][38][39][40][41][42] Castleman's disease (in Japan) [52,53] Systemic and polyarticular JIA (in Japan) [57][58][59] Candidate diseases for tocilizumab therapy: Systemic autoimmune diseases SLE [130] Systemic sclerosis [115] Giant cell arteritis and Takayasu arteritis [90,91] Polymyositis Organ specific autoimmune diseases Crohn's disease [73] Relapsing polychondritis [108] Multiple sclerosis, neuromyelitis optica Acquired hemophilia A [149] Chronic inflammatory diseases Adult-onset Still's disease [61][62][63][64][65][66][67][68] Reactive AA amyloidosis [48][49][50][51] Polymyalgia rheumatica [80,91] RS3PE [85] Spondyloarthritides [100,[102][103][104][105] Behcet's disease Uveitis GVHD [150] Autoinflammatory diseases (TRAPS) [152] Tocilizumab has been approved as a biological drug for the treatment of RA, Castleman's disease and juvenile idiopathic arthritis, and is expected to be applicable to various other autoimmune and inflammatory diseases. Abbreviations: RA, rheumatoid arthritis; JIA, juvenile idiopathic arthritis; SLE, systemic lupus erythematosus; RS3PE, remitting seronegative, symmetrical synovitis with pitti...…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…There are also case reports in regards to the use of tocilizumab in other auto-immune conditions such as giant cell arteritis [30,31], adult onset Still's disease [32] , systemic lupus erythematosus [33], ANCA-associated vasculitis [34], Behcet's disease [35,36], systemic sclerosis [37] and polymyositis [38]. These reports showed that tocilizumab was the salvage therapy used after disease resistance to various former drugs.…”
Section: Tocilizumab and Other Il-6 Agents Currently Under Developmentmentioning
confidence: 99%
“…These histological findings are very similar with previous findings in scleroderma patients treated with tocilizumab. 26 These patients showed softening of the skin with reductions of Vesmeter hardness, and similar histological changes. 26 Thickness of the collagen fiber bundles but not dermal thickness may be important in skin softening in scleroderma.…”
Section: Discussionmentioning
confidence: 76%